PATOLOGI SOSIAL DALAM NOVEL DI BAWAH UMUR KARYA ERISCA FEBRIANI DAN SUKHDEV SINGH DAN RELEVANSINYA DENGAN PEMBELAJARAN BAHASA INDONESIA DI SMA - Wahyuni, Primasari (Bahterasia : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
Literary works are works of the author's imagination which are expressed in the form of ideas, ideas about life experiences and various problems in the surrounding environment. Literary works cannot be separated from the reality that occurs in society. One example of problems in social life described by authors in literary works is social pathology. Social pathology can be called a form of abnormal individual behavior in social life, whether visible or invisible. This research aims to (1) describe the social pathology in the novel Di Bawah Umur by Erisca Febriani and Sukhdev Singh, (2) describe the relevance of the novel Di Bawah Umur by Erisca Febriani and Sukhdev Singh in learning Indonesian.  This research data is in the form of words, phrases and sentences in the novel Underage by Erisca Febriani and Sukhdev Singh which contains social pathology. The data were analyzed using Wellek and Warren's literary sociology approach which focused on the second study, namely the sociology of the content of literary works.  The data collection technique used is the reading and note taking technique. The data analysis technique used is content analysis.  Based on the results of data analysis, social pathology in the novel Underage by Erisca Febriani and Sukhdev Singh includes juvenile delinquency, prostitution, pornography and alcoholism. The results of this research can be relevant to Indonesian language learning in analyzing the content and language of novels.